2022
DOI: 10.9734/jamps/2022/v24i11587
|View full text |Cite
|
Sign up to set email alerts
|

Practices and Barriers towards Pharmacovigilance and Adverse Drug Reporting among Intern Pharmacists in Nigeria

Abstract: Background: The practice of Pharmacovigilance (PV) and Adverse Drug Reaction (ADR) reporting is very necessary to ensure adequate safety of all drugs in use and is an integral component of post marketing surveillance. Pharmacist, including interns are at a central position in carrying out this important function. Objectives: This study sought to assess the practice of  pharmacovigilance and adverse drug reaction reporting and the perceived barriers towards its implementation among pharmacist interns in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Studies have identified various issues within the country's pharmacovigilance system. One critical aspect is the underreporting of adverse drug reactions (ADRs), which is crucial for effective pharmacovigilance ( Pharmacists, including interns, play a central role in pharmacovigilance activities, but they encounter barriers such as inadequate reporting practices and perceived challenges in implementation (Eze et al, 2022). Additionally, the lack of standardized ADR reporting forms and formal reporting systems at healthcare centers presents a significant obstacle that requires immediate attention (Adeleke et al, 2019; Adisa & Omitogun, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have identified various issues within the country's pharmacovigilance system. One critical aspect is the underreporting of adverse drug reactions (ADRs), which is crucial for effective pharmacovigilance ( Pharmacists, including interns, play a central role in pharmacovigilance activities, but they encounter barriers such as inadequate reporting practices and perceived challenges in implementation (Eze et al, 2022). Additionally, the lack of standardized ADR reporting forms and formal reporting systems at healthcare centers presents a significant obstacle that requires immediate attention (Adeleke et al, 2019; Adisa & Omitogun, 2019).…”
Section: Introductionmentioning
confidence: 99%